2012
DOI: 10.1007/s12282-012-0380-z
|View full text |Cite
|
Sign up to set email alerts
|

Marked lymphovascular invasion, progesterone receptor negativity, and high Ki67 labeling index predict poor outcome in breast cancer patients treated with endocrine therapy alone

Abstract: The results of this multi-institute cohort study indicated that endocrine therapy alone could not prevent distant metastasis in breast cancer patients with PgR-negative tumors and/or with tumors showing marked LVI or high cell proliferation. These patients may need postoperative adjuvant chemotherapy in addition to endocrine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…23 However, these findings are not without controversy, as several groups found that ALDH1 expression did not correlate with clinical parameters and was not an independent prognostic factor in breast cancer. 10,33 In our cohort, we observed ALDH1 expression in both the DCIS epithelial compartment and the local stroma environment. ALDH1 protein levels in either compartment were not statistically associated DCIS recurrence or invasive progression, although ALDH1 expression with the DCIS lesion trended toward increased risk.…”
mentioning
confidence: 67%
“…23 However, these findings are not without controversy, as several groups found that ALDH1 expression did not correlate with clinical parameters and was not an independent prognostic factor in breast cancer. 10,33 In our cohort, we observed ALDH1 expression in both the DCIS epithelial compartment and the local stroma environment. ALDH1 protein levels in either compartment were not statistically associated DCIS recurrence or invasive progression, although ALDH1 expression with the DCIS lesion trended toward increased risk.…”
mentioning
confidence: 67%
“…1 More than half of newly diagnosed Japanese breast cancer patients are estimated to have node-negative, invasive disease, resulting in local or distant recurrence within 10 years of the diagnosis in 10% to 15% of these patients. 2,3 Therefore, it has been important to establish criteria for identifying the high-risk patient groups for whom adjuvant chemotherapy might be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells proliferation is an important biological parameter that reflects disease behavior, which might also predicts for disease prognosis. The nuclear protein Ki-67 is a proliferative marker and widely used prognostic indicator in several cancer diagnosis, including breast cancer, bladder cancer, gastrointestinal neuroendocrine tumor, oral cancer, lung cancer, astrocytoma, and pituitary adenoma [8][9][10][11][12]23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The Ki-67 protein is an (IHC) marker of cell proliferation associated nuclear antigen which is expressed in dividing cells during cell cycle (G1, S, G2 and M) but not on (G0) [6,7]. The labeling index of Ki-67 has a direct correlation with the degree of cells proliferation, and has prognostic value in several types of cancer [8][9][10][11][12]. The Ki-67 is a commonly used proliferation marker in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation